Adsorption of Cu(II) in Aqueous Solution by Modified Sawdust Cellulose. (February 2019) - Ulfa, Siti Mariyah; Chamidah, Nur; Kurniawan, Andi
Abstract: The utilization of modified sawdust cellulose and the adsorption capacity for Cu(II) removal in aqueous solution is reported. The modification of cellulose was conducted by delignification using NaOH followed by esterification using citric acid. Delignification sawdust (DLSD) using NaOH 0.5 M gave the increasing cellulose content to 22.38%. Then, the esterification of cellulose using 1.2 M of citric acid successfully increasing the hydroxyl and carboxyl group from the analysis of FTIR. The modified sawdust (MDSD) showed the increasing intensity of -OH stretching in in 3348 cm −1 in concomitant with the emergence of a new peak at 1717 cm −1 identified as C=O, either from carboxyl and/or carbonyl moieties. Adsorption capacities of DSLD and MDSD for Cu(II) are evaluated in constant pH 6. The maximum adsorption of MDSD is achieved within 2 h and adsorbed 78.3% of Cu(II). The adsorption of Cu(II) is fitted well with the Langmuir model suggesting the physical interaction between -OH and/or COO − with the metal cation. The adsorption capacity of Cu(II) by MDSD is 4.33 mg/g higher than DSLD which is 2.61 mg/g. Based on this result, modification of sawdust cellulose increased the adsorption capacity of Cu(II) in aqueous solution.